AFFECTIVE AND PRACTICAL COMMUNICATION IN PLAYFUL ACTIVITIES IN EARLY CHILDHOOD: WHAT TO GET FROM A BOOK IN THE PROCESS OF CHILD HUMANIZATION? - Guizelim Simoes Girotto, Cyntia Graziella [UNESP] (Fundacao Univ Tocantins, 2017)
The essay presented here results from a bibliographical-theoretical research, whose central focus was to understand the relationship between child development and the offer and mediation of books in early childhood, in the quest to understand the relevance of children's experiences with the book object Material read in the process of humanizing children. For this, the concepts addressed, in the text, are based on the assumptions of the vygotskian school. The results point to the need to deepen the studies on the specificities of the little ones, as a guiding basis for thinking about productive and welcoming reading practices in this stage of life.
Keywords: Early Childhood and books; Affective and practical communication; Children's literature and humanization of children; Mediation of literary